Análisis psicométrico del cuestionario de clima laboral de la Fuerza Aérea Colombiana (2012)
The purpose of the study was to propose an instrument in order to measure the work environment in the Colombian Air Forces. In order to do this, a questionnaire of work environment was designed; then the psychometric characteristics were evaluated and the utility as an instrument of measurement was established. This study was instrumental and 3272 military servants took part in it and were classified according to their rank, branch where they work, if they were the chief of a division and location in the national territory. In order to identify the discriminative potential of each one of the items to differentiate among the military servants who have a high perception of a good work environment and those who do not have it, each item was analyzed. Homogeneity and inner consistency were also studied. All the scales got an alpha bigger than 0,72 and according to each item, a scale of 58 items is proposed. It was concluded that the questionnaire of work environment has a good homogeneity and discriminative capacity.